CURRENT PROBLEMS OF WASTE DISPOSAL OF TREATMENT AND PREVENTIVE INSTITUTIONS (LITERATURE REVIEW) (Modern American Journal of Medical and Health Sciences, 2025)
The organization of a system for handling hospital waste has special features due to the relevance of the potential risk of interacting with it and the polymorphism of this type of waste. This is reflected in such regulatory documents as “Sanitary rules, norms and hygiene standards for the design, construction and operation of treatment and prevention institutions” (SanQva N No. 0020-22) and “Sanitary rules and norms for the collection, storage and utilization of waste in medical institutions of the Republic of Uzbekistan” (SanPiN No. 0317-15 of the Republic of Uzbekistan). Subject to the recommendations of sanitary rules and norms, the need to use thermal processing technology for hospital waste is introduced only for waste of classes B and V, which have an epidemiological hazard and are contaminated with biological fluids of patients. At the same time, the problem of the level of their necessary sanitation arises, that is, it is necessary to determine whether disinfection of such waste is sufficient or whether sterilization or complete replacement of the waste substrate should be used [4,7].